Physico-Chemical Analysis of Panchagavya Ghritha Prepared as per Ashtanga Hridaya Reference and Comparison with Market Samples - Lakshmi P N,; Sreeni T V, (International Journal of Ayurveda and Pharma Research, 2022)
Panchagavya Ghritha is a widely used Ayurvedic formulation mentioned in Ashtanga Hridaya Utharastana Apasmara Patishedha indicated in conditions like Apasmara (epilepsy), Jwara (pyrexia), and Kamala (jaundice). It contains 5 ingredients namely Goshakrit rasa (cow dung juice), Amladadhi (sour curd), Goksheera (cow’s milk), Gomutra (cow’s urine) and Goghritha (ghee). Authentic sources of cow products are not often obtained and found adulterated. Collection and processing of fresh raw materials are an important area in this formulation This study was conducted to find out the non conformances and quality issues in Panchagavya ghritha production in industrial level. The comparative analysis of prepared and market samples based on standard analytical parameters proposed by PLIM reveals the variation in different organoleptic characters and physico-chemical parameters. The physico-chemical parameters among prepared and different companies were statistically analysed with ANOVA test and Scheffe’s pair wise comparison, showed significant difference at 0.01 levels.